Contained-Opposition, Opposition Movements in Indonesia: A Case Study of ICMI - Nanang Tahqiq (Refleksi, 2000)
Many inquiries have been made about the existence of Ikatan Cendekiawan Muslim Indonesia (ICMI - phonetically: Each Me - Asociaton of Indonesian Muslim Intellectuals), notably after Bachruddin Jusuf Habibie resigned form the presidency, and 'Gus Dur' (a nickname of Abdurrahman Wahid) was elected as the new president of Indonesia (the fourth president) for the period 1999-2004.